Modelling predictors of students' learning gain - an empirical evidence using structural equation modelling / Nor Aini Hassanuddin, Sakinah Mat Zin and Rohana Yusoff - Hassanuddin, Nor Aini; Mat Zin, Sakinah; Yusoff, Rohana (Research Management Institute (RMI), 2013)
The abundance of literature on effective teaching that relates to student achievement bears witness to the ongoing quest for a better understanding of the effect of lecturers' characteristics and attributes (inputs) on students' learning gain. What is rarely looked at is how lecturers actually performs in the classroom and how that performance translates into students' learning advantage. The aim of this paper is to provide an in-depth analysis of the relationship between the lecturers' teaching contribution and students' learning gain. The methods of analysis start with establishing construct validity of the instrument through confirmatory factor analysis (CFA), using Analysis of Moment Structures software (AMOS). Data from this study were further analyzed with Structural Equation Modelling (SEM). All four dimensions of the lecturers' teaching attributes; namely rapport, clear explanation, preparation and organization, and feedback are considered as independent variables and students' learning gain as the dependent variable. The results of this study indicate that among the four teaching dimensions examined, the significant predictors of students' learning gain in the process of teaching and learning are clear explanation and lecturers' feedback.